Appetitive and Metabolic Responses to an Exercise versus Dietary Intervention in Adults with Obesity. Issue 4 (14th October 2022) - Purcell, Sarah A.; Legget, Kristina T.; Halliday, Tanya M.; Pan, Zhaoxing; Creasy, Seth A.; Blankenship, Jennifer M.; Hild, Allison; Tregellas, Jason R.; Melanson, Edward L.; Cornier, Marc-Andre
ABSTRACT: Introduction/Purpose: Dietary restriction (DIET) and aerobic exercise (AEX) interventions may affect energy balance differently. Our aim was to describe the effects of weight loss interventions via DIET or AEX on measures of energy balance. Methods: Adults with overweight or obesity were randomized to 12 wk of DIET or AEX with similar calorie deficit goals. A study day was conducted before and after the intervention to assess subjective and hormonal (ghrelin, peptide-YY, glucagon-like peptide-1) appetite responses to a control meal, ad libitum energy intake (EI) at a single meal, and over 3 d of free-living conditions and eating behavior traits. Resting metabolic rate was measured with indirect calorimetry and adjusted for body composition measured by dual-energy x-ray absorptiometry. Nonexercise activity was measured using accelerometers. Results: Forty-four individuals were included (age, 37 ± 9 yr; body mass index, 30.6 ± 3.1 kg·m −2 ). Both interventions resulted in weight and fat mass loss. The DIET group lost fat-free mass, although differences between groups were not significant (DIET = −1.2 ± 1.7 kg, P < 0.001; AEX = 0.4 ± 1.5 kg, P = 0.186; P = 0.095 interaction). There were no differences in resting metabolic rate after body composition adjustment. Both interventions were associated with an increase in dietary restraint (DIET = 4.9 ± 1.2; AEX = 2.8 ± 0.7; P < 0.001 in both groups). Hunger decreased with DIET (−1.4 ± 0.5, P = 0.003), and disinhibition decreased with AEX (−1.5 ± 0.5, P < 0.001), although these changes were not different between groups (i.e., no group–time interaction). No other differences in appetite, EI, or nonexercise physical activity were observed within or between groups. Conclusions: AEX did not result in compensatory alterations in appetite, ad libitum EI, or physical activity, despite assumed increased energy expenditure. Modest evidence also suggested that disinhibition and hunger may be differentially affected by weight loss modality.